Revisiting the phenotypic and genetic profiling of anergic T cells mediating long-term transplant tolerance. Issue 1 (February 2018) - You, Sylvaine; Chatenoud, Lucienne
Abstract : Purpose of review: Herein our focus will be to revisit peripheral tolerance mechanisms and in particular 'active' or 'dominant' tolerance as originally defined and mediated by regulatory CD4 + FoxP3 + T lymphocytes (Treg) and also T-cell anergy that appears as a major mainstay to support long-term allograft survival. Recent findings: It is at the same time interesting and rewarding that the tool that recently guided our efforts along this path is the in-vivo use of CD3 antibody, the first monoclonal introduced in the clinic (Orthoclone OKT3) about 35 years ago to treat and prevent rejection of renal allografts. Beyond their immunosuppressive activity, whenever administered judiciously, CD3 antibodies promote robust allograft tolerance through selective purging of alloreactive effectors, resetting Treg-mediated active tolerance and promoting a unique subset of anergic CD8 + T cells. Summary: The new findings discussed open up new perspectives from both a fundamental and a clinical point of view. In basic research, concrete molecular signaling paths are now spotted to finely dissect the conditions that lead to the establishment and maintenance of robust T-lymphocyte anergy mediating allograft tolerance. In the clinic, this may rapidly translate into novel biomarkers to be used in parallel to the ones already available, to better adapt posttransplant immunotherapy and monitor for long-term allograft acceptance.